Investigation of informed consent procedures initiated in the intrapartum period. (2nd April 2020) - Alvarez, Mary; Hotton, Emily; Harding, Sam; Crofts, Joanna F; Wade, Julia
Abstract : Background: When research involves procedures initiated in the intrapartum period, there is considerable variation in information provision. If midwives are to optimise the process of information provision and facilitate good understanding of the research, we need to understand how information is currently being provided. Aim: To investigate the feasibility and acceptability of an approach to investigating information provision for informed consent to research involving interventions initiated during the intrapartum period. Methods: Audio recordings of seven study recruitment consultations and six structured interviews were transcribed and analysed to construct a 'hints and tips' for recruitment document for midwives. Findings: Most women and three out of five midwives agreed to audio-recording consultations. All participants confirmed the acceptability of audio-recording recruitment consultations. Midwives varied in their experiences. Conclusion: This approach to exploring the informed consent processes is feasible and acceptable to women and midwives. Findings will inform further investigation of information provision in the ASSIST II study.